iSeizdiag: toward the framework development of epileptic seizure detection for healthcare - Sharma, Ashish; Saxena, Akshat; Agrawal, Mradul; Kishor, Kunal; Kaushik, Deepti; Jain, Prateek; Yadav, Arvind R.; Saikia, Manob Jyoti (Frontiers in Computational Neuroscience, 2025)
IntroductionThe seizure episodes result from abnormal and excessive electrical discharges by a group of brain cells. EEG framework-based signal acquisition is the real-time module that records the electrical discharges produced by the brain cells. The electrical discharges are amplified and appear as a graph on electroencephalogram systems. Different neurological disorders are represented as different waves on EEG records.MethodThis paper involves the detection of Epilepsy which appears as rapid spiking on electroencephalogram signals, using feature extraction and machine learning techniques. Various models, such as the Support Vector Machine, K Nearest Neighbor, and random forest, have been trained, and accuracy has been analyzed to predict the seizure.ResultAn average accuracy of 95% has been claimed using the optimized model for epileptic seizure detection during training and validation. During the analysis of multiple models, the 97% accuracy is claimed after testing. Some statistical parameters are calculated to justify the optimized framework.DiscussionThe proposed approach represents a satisfactory contribution in precise detection for smart healthcare.